Nazwy miejscowe w małopolskich rotach przysiąg sądowych (1399–1418) .......... 485 - Przęczek-Kisielak, Sylwia (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
PLACE NAMES IN LESSER POLISH JUDICIAL OATHS (1399–1418) The article combines a lexicographic description of place names recorded in 96 Lesser Polish judicial oaths (both in Polish texts and Latin preambles), dated 1399–1418, edited by B. Ulanowski in 1884 in „Sprawozdania Komisji Językowej Akademii Umiejętności”, with a semantic-structural analysis according to W. Taszycki’s typology of place names. The collected material, totaling 107 toponyms, has been divided into seven semantic groups and sorted in statistical order: possessive names (36.1%), patronymic names (35.1%), topographic names (19.6%), occupational names (3.1%), ethnic, cultural and unclear names (2.1% each). The names have been cross-referenced with the major onomastic dictionaries from the area of Lesser Poland (including K. Rymut’s Nazwy miejscowe północnej części dawnego województwa krakowskiego [‘Place names from the northern part of the former Cracow voivodeship’], W. Lubaś’s Nazwy miejscowe południowej części dawnego województwa krakowskiego [‘Place names from the southern part of the former Cracow voivodeship’], K. Rymut’s Patronimiczne nazwy miejscowe w Małopolsce [‘Patronymic place names in Lesser Poland’] and Słownik historyczno-geograficzny ziem polskich w średniowieczu [‘A historical-geographical dictionary of Polish lands in the Middle Ages’]), and the results compared with the findings of a similar analysis of place names from the earliest Lesser Polish judicial oaths from 1397–1399. Within each semantic type, a structural description of the collected toponyms was proposed, that classifies them based on the personal name from which they are derived (possessive and patronymic names), words describing the topographic features of the area in which they are located (topographic names), elements of material and spiritual culture (cultural names), activities and functions performed by the inhabitants (occupational names), and finally suffixes used in their formation (possessive, patronymic, topographic, occupational, and ethnic names); in each group, the most productive unit has been indicated. Collected and analysed in this manner, the material offers insight into the process of creation of place names, and into a certain stage in their development during the 13th and 14th centuries.